Ropivacaine versus Bupivacaine for 3-in-l Block during Total Knee Arthroplasty. (December 2013) - Theodosiadis, Panagiotis; Sachinis, Nick; Goroszeniuk, Teo; Grosomanidis, Vasilios; Chalidis, Byron
Purpose: To compare the use of ropivacaine versus bupivacaine for 3-in-1 block during total knee arthroplasty (TKA) in terms of efficacy and safety (lack of toxicity). Methods: 14 men and 26 women aged 58 to 77 (median, 70) years who had the American Society of Anesthesiologists (ASA) grades I to III physical status were randomised to receive ropivacaine (n=20) or bupivacaine (n=20) of a concentration of 0.5% for 3-in-1 block during TKA. The dosage was 0.5 ml/kg. In addition, a sciatic nerve block (20 ml of prilocaine 1%) was used. The onset of the block, duration of postoperative analgesia, level of motor block, and any side-effects were compared. Results: The median time to onset of block was significantly shorter in those receiving ropivacaine than bupivacaine (13 vs. 17.5 minutes, p<0.001), but the levels of motor blockade were not significantly different (p=0.355). Complete analgesia was achieved throughout the procedure. There was no significant difference between the ropivacaine and bupivacaine groups in terms of the mean duration of analgesia (398 vs. 367 minutes, p=0.62), the mean VAS scores at all time points, and the mean total morphine consumption. One patient in the ropivacaine group developed a joint haematoma and 2 patients in the bupivacaine group had excessive wound drainage. Both conditions resolved after antibiotic use. Conclusion: Ropivacaine and bupivacaine showed similar anesthetic and analgesic effects, but the former had a significantly faster onset time.